Promising Essential Oils/Plant Extracts in the Prevention and Treatment of Dandruff Pathogenesis - Kumari, KM U.; Yadav, Narayan Prasad; Luqman, Suaib (Current Topics in Medicinal Chemistry, 2022)
Background: Dandruff is a scalp disorder affecting the male populace predominantly. Topical agents and synthetic drugs used for dandruff treatment have specific side effects including burning at the application site, depression, dizziness, headache, itching or skin rash, nausea, stomach pain, vision change, vomiting, discoloration of hair, dryness or oiliness of the scalp and increased loss of hair. Thus, essential oils and extracts from plants could be valuable in the treatment and prevention of dandruff. Aims & Objectives: This review aims to highlight current findings in dandruff occurrence, its etiology, promising plant essential oils/extracts, and novel treatment strategies. The main emphasis has been given on the anti-dandruff effect of essential oils and plant extracts to disrupt microbial growth. The proposed mechanism(s) of action, novel approaches used to perk up its biopharmaceutical properties, and topical application have been discussed. Results: The literature survey was done, and bibliographic sources and research papers were retrieved from different search engines and databases, including SciFinder, PubMed, NCBI, Scopus, and Google Scholar. The selection of papers was accomplished based on exclusion and inclusion criteria. The scalp of diverse populations revealed an association of dandruff with microbial symbiosis, including Staphylococcus, Propionibacterium, Malassezia, and Candida as the pathogens responsible for the cause of dandruff. Topical antifungals are considered the first line of treatment for dandruff including azoles, with clotrimazole (1%), ketoconazole (2%), and miconazole (2%). Other commonly used therapies integrate benzoyl peroxide, coal tar, glycerin, zinc pyrithione, lithium succinate/gluconate, salicylic acid, selenium disulfide/sulfide, sodium sulfacetamide, etc. However, these medicaments and chemicals are known to cause specific side effects. Alternative therapies, including tea tree oil, thyme, Aloe vera, Mentha have been reported to demonstrate anti-dandruff activity by disrupting the microbial growth associated with dandruff formation. Conclusion: Overall, this review explains the occurrence of dandruff, its pathogenesis, and the potential applicability of promising plant essential oils/extracts and their novel treatment strategies. Further studies based on pre-clinical and clinical research are essential before making any conclusion about its efficacy in humans.
Keywords: Keratin